"I have just returned from the moon:" online survey fraud. Issue 4 (27th March 2020) - Brazhkin, Vitaly
Abstract : Purpose: The purpose of this paper is to provide a comprehensive review of the respondents' fraud phenomenon in online panel surveys, delineate data quality issues from surveys of broad and narrow populations, alert fellow researchers about higher incidence of respondents' fraud in online panel surveys of narrow populations, such as logistics professionals and recommend ways to protect the quality of data received from such surveys. Design/methodology/approach: This general review paper has two parts, namely, descriptive and instructional. The current state of online survey and panel data use in supply chain research is examined first through a survey method literature review. Then, a more focused understanding of the phenomenon of fraud in surveys is provided through an analysis of online panel industry literature and psychological academic literature. Common survey design and data cleaning recommendations are critically assessed for their applicability to narrow populations. A survey of warehouse professionals is used to illustrate fraud detection techniques and glean additional, supply chain specific data protection recommendations. Findings: Surveys of narrow populations, such as those typically targeted by supply chain researchers, are much more prone to respondents' fraud. To protect and clean survey data, supply chain researchers need to use many measures that are different from those commonly recommended in methodological survey literature. Research limitations/implications: For the first time, the need to distinguish between narrow and broad population surveys has been stated when it comes to data quality issues. The confusion and previously reported "mixed results" from literature reviews on the subject have been explained and a clear direction for future research is suggested: the two categories should be considered separately. Practical implications: Specific fraud protection advice is provided to supply chain researchers on the strategic choices and specific aspects for all phases of surveying narrow populations, namely, survey preparation, administration and data cleaning. Originality/value: This paper can greatly benefit researchers in several ways. It provides a comprehensive review and analysis of respondents' fraud in online surveys, an issue poorly understood and rarely addressed in academic research. Drawing from literature from several fields, this paper, for the first time in literature, offers a systematic set of recommendations for narrow population surveys by clearly contrasting them with general population surveys.